TAX AUDITOR’S ETHICS REVIEW FROM ISLAMIC PERSPECTIVE (AT REGIONAL OFFICE OF DGT EAST JAVA I) - Faturachman, Dedy; Puspitorini, Gayatri Indah (Universitas Muhammadiyah Surakarta, 2022)
Ethics currently exists in various professions. Tax auditors have been provided with a code of ethics that must be obeyed. Islam is a religion that teaches the values of goodness and the basic beliefs of its people in living life. In this article the authors want to explain the importance of ethics from an Islamic point of view in the tax auditor profession. The research was conducted using descriptive qualitative methods, in the form of field research. The results of the study indicate that the existing professional ethics of tax auditors are in accordance with Islamic teachings, in carrying out their duties and work a tax auditor must apply existing professional ethics and implement Islamic teachings.